Social Interaction of Teenage Mothers During and After Their Pregnancy - F.P.R. de Villiers; J. Kekesi (South African Family Practice)
Extensive attention has been given to adolescent sexuality and teenage pregnancy in the past 30 years, yet many teenagers still fall pregnant. A teenager who becomes a parent is at a significant disadvantage in becoming a contributing adult, both psychosocially and economically. The objective of the study was to describe the social interaction of teenage mothers at Ga-Rankuwa Hospital during and after their pregnancy. Seventy teenage mothers were interviewed using an interview schedule. Thirty-four of them stayed with both parents, 19 with the mother only and the rest with relatives or their partner's mother. Only one was married (by customary law), and most (59%) had known their partner for 12–24 months. Fifty-two talked to someone when they discovered that they were pregnant, nine were too scared to do so and the other nine were unaware of the pregnancy until it was discovered by a family member. Most (58) wished to return to school within a year, seven wished to find work (after first looking after the baby), and two wished to get married. In conclusion, the majority of teenagers who fall pregnant do so while still at school. Teenagers are at risk of unwanted pregnancies. Few first tell their mothers about the pregnancy, although most talk to someone soon after discovering that they are pregnant. Most, however, retain the support of their families during and after the pregnancy.